Haloperidol for Pain Management: A Narrative Review - Carlos J. Roldan; Jonathan W. Rowland; Alice L. Ye (MDPI AG, 2024)
The use of haloperidol in pain management has been a topic of interest for several decades. Haloperidol is a widely used antipsychotic medication with unique pharmacologic properties that make it a potential candidate for pain management. However, the efficacy and safety of haloperidol for pain management remain controversial. This narrative review provides a summary of the current literature on the use of haloperidol for pain management, including its pharmacology, clinical effectiveness, adverse effects, and dosing regimens. We performed a comprehensive search of the literature for this review. The most robust clinical data from the past decade suggest that haloperidol has good efficacy in the treatment of pain related to gastroparesis and migraines and has shown promise for opioid use reduction in patients with chronic pain or receiving palliative care. The overall side effect profile is excellent, with zero reported events of QT-related cardiac arrest and minimal reports of sedation and transient extrapyramidal effects such as akathisia. Dosing regimens used were heterogeneous, with most ranging from 1 to 5 mg per dose via intravenous, intramuscular, or oral route. Studies with designs that isolated the effects of haloperidol from combinations of other drugs were extremely limited. Further high-quality prospective studies are needed to determine the ideal role of haloperidol in the routine clinical management of painful conditions.